Biotar ironmaking using wooden biomass and nanoporous iron ore - Hata, Yuichi; Purwanto, Hadi; Hosokai, Sou; Hayashi, Jun-ichiro; Kashiwaya, Yoshiaki; Akiyama, Tomohiro (American Chemical Society (ACS Publications), 2009)
This paper describes fundamental experiments of a new biomass ironmaking that employs low-grade iron ore and woody biomass for promoting the direct reduction, FeO + C ) Fe + CO, in which dehydrated, porous limonite iron ore was filled with carbon deposited from the biomass tar, biotar. In our experiments, three types of iron ores containing different amounts of combined water (CW; 1.6, 3.8, and 9.0 mass %) were first dehydrated at 450 °C to make them porous and then heated with pine tree biomass at 500-600 °C for the gasification and the tar vapor generated was decomposed to deposit carbon within/on the porous ores. The dehydration treatment made the iron ores porous by removing CW and significantly increased their Brunauer-Emmett-Teller (BET) specific surface areas and porosities. In the second treatment of biomass gasification and decomposition of tar vapor, the biomass was changed into char, tar vapor, and reducing gas; the biotar was decomposed and carbonized within the porous ores. Interestingly, the ores caught biotar effectively, not only on the surface but also inside their pores. Here, the ores with the nanosized pores served as catalysts for tar carbonization with gas generation. Simultaneously, the ores were partially reduced to magnetite by the reducing gas. The ores containing carbonized material were easily reduced to iron by only heating until 900 °C in a nitrogen atmosphere; this was due to the direct contact of carbon and iron oxide within the ores, so-called direct reduction. In conclusion, the dehydrated limonite iron ore was most effective for avoiding the generation of sticky tar in the biomass gasification and for filling the porous ore with carbon from tar. The product is a promising raw material for biomass ironmaking. The results appealed an innovative ironmaking method with a large reduction of carbon dioxide emission using low-grade iron ore and woody biomass.